Hand carriage of Candida occurs at lesser rates in hospital personnel who use antimicrobial hand disinfectant. (September 2014) - Yildirim, Mustafa; Sahin, Idris; Oksuz, Sukru; Sencan, Irfan; Kucukbayrak, Abdulkadir; Cakir, Selma; Ozaydin, Cigdem
Abstract Background: The hands of hospital personnel are considered to be important for colonization and infection of patients with Candida spp. The aim of this study was to evaluate the effectiveness of different hand disinfectants in reducing the carriage of Candida species on the hands of hospital personnel. Methods: A controlled study was conducted at Duzce University School of Medicine Hospital. Eighty hospital personnel were included in the trial. Subjects were divided into 4 groups according to hand hygiene procedures: group 1, hand rubbing with alcohol-based solution; group 2, hand washing with 4% chlorhexidine gluconate; group 3, hand washing with 7.5% povidone–iodine; group 4, hand washing with plain soap and water. The hands of all participants were tested by culture with the broth wash technique. Results: Hand carriage of Candida spp. was lower in the 4% chlorhexidine gluconate group (10.5%, p = 0.006), in the 7.5% povidone–iodine group (18.7%, p = 0.043), and in the alcohol-based hand rub group (21.1%, p = 0.048) compared to the group washing hands with plain soap and water (50%). Conclusions: The use of hand disinfectant containing antimicrobial agents is more effective than hand washing with water and soap in reducing carriage of Candida on the hands of hospital personnel. It is recommended that hospital personnel use an antimicrobial hand disinfectant in units where there is a high risk of Candida infection.